APLIKASI ANALYTIC HIERARCHY PROCESS (AHP) DALAM PEMILIHAN SISWA TELADAN - Hafiyusholeh, Mohammad (saintis, 2009)
AHP (Analytic Hierarchy Process) can be applied in the selection of model student. From the structure of a complex, unstructured, and then formed a hierarchical structure. In the hierarchy itself there is the main goal or objective to be achieved, criteria, sub-criteria, and alternatives. From here, the decision maker then makes a comparison in pairs for obtaining priority of all the available alternatives. The results of this pair wise comparison matrix, which will form the ratio scale derived in the form of Eigen vectors. Generally there are three principles that became an integral part in constructing the AHP: decomposition, comparative judgments, and synthesis of priority.